Oral Presentations Abstracts: EUTHANASIA AND WITHDRAWAL OF TREATMENT IN PEOPLE WITH DISABILITIES AND INTRACTABLE DISEASES: COMPARISON BETWEEN JAPAN AND WESTERN COUNTRIES - TANAKA, Miho; KODAMA, Satoshi (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Background: In Japan, groups advocating for people with disabilities and intractable diseases (hereafter “PWDs”) have recently voiced serious concerns regarding end-of-life care policies. For example, when non-partisan MPs announced a draft bill on allowing forgoing life-sustaining treatments (LSTs) in 2012, these groups protested. One group in particular strongly protested against a TV documentary by the Japanese public broadcasting corporation in 2019, in which a patient with a serious neurologic intractable disease died by physician-assisted suicide in Switzerland. Objective: To present the specific concerns voiced by PWDs regarding end-of-life care policies and to compare debates between Japan and Western countries on the topic. Method: Comprehensive literature review. Results: Several important points emerged. In Japan, PWDs felt that those living with LSTs would consider it a life without dignity. In Western countries, the following issues surfaced: negative images of people with disabilities have deep roots in society due to the long and tragic history of discrimination; people with disabilities might become victims of society’s value judgment, such as “life with a severe disability is not worth living”; and laws and safeguard policies cannot eliminate the concerns of a slippery slope. Conclusion: Western countries have recently discussed the risks of legalising euthanasia, while discussions in Japan have focused more on the risks of legislation on forgoing LSTs. Future literature review studies and interviews with advocacy groups aimed at identifying similar situations in other East Asian countries are warranted.